2022
DOI: 10.1111/ijcs.12801
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking consumer consideration set size formation for luxury services: A study of self‐identification, brand status and anticipated emotions

Abstract: With a wide array of services touting their luxury and status appeal, consumers must make choices in an increasingly contested marketspace. The choice of luxury services can be complex and entail uncertainty and risk. In an attempt to understand factors that influence consumers’ choices regarding luxury services, this study explores consumers’ consideration set size, the role of self‐identification with the service brand, positive anticipated emotions about using the service brand, and perception of the brand'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 88 publications
0
0
0
1
Order By: Relevance
“…Biological/personal/ demographic (Bae & Jo, 2024;Creevey et al, 2022;Dhaliwal et al, 2020;Dubois et al, 2021;Kunz et al, 2020) Psychological factors (Creevey et al, 2022;Dubois et al, 2021;Gupta, Shin, & Jain, 2023;Gurzki & Woisetschläger, 2017;Husain et al, 2021;Siahtiri et al, 2022) Macro/structural factors (Dubois et al, 2021;Gurzki & Woisetschläger, 2017) Social cultural and intercultural factors (Arli et al, 2020;Dhaliwal et al, 2020;Gupta, Shin, & Jain, 2023;Gurzki & Woisetschläger, 2017;Husain et al, 2021;Sun et al, 2014;Tunçel, 2022) Branding (Bilro et al, 2022;Creevey et al, 2022;Dhaliwal et al, 2020;Dubois et al, 2021;Gupta, Shin, & Jain, 2023;Gurzki & Woisetschläger, 2017;Husain et al, 2021;Kola nska-Stronka & Krasa, 2023;Kunz et al, 2020;Purohit et al, 2023;Shimul & Phau, 2022;Siahtiri et al, 2022) Counterfeiting (Gurzki & Woisetschläger, 2017;Husain et al, 2021;Shan et al, 2022;Tunçel, 2022) Sustainability (Atkinson & Kang, 2021;Kunz et al, 2020;…”
Section: Main Themes/drivers Scholarsunclassified
“…Biological/personal/ demographic (Bae & Jo, 2024;Creevey et al, 2022;Dhaliwal et al, 2020;Dubois et al, 2021;Kunz et al, 2020) Psychological factors (Creevey et al, 2022;Dubois et al, 2021;Gupta, Shin, & Jain, 2023;Gurzki & Woisetschläger, 2017;Husain et al, 2021;Siahtiri et al, 2022) Macro/structural factors (Dubois et al, 2021;Gurzki & Woisetschläger, 2017) Social cultural and intercultural factors (Arli et al, 2020;Dhaliwal et al, 2020;Gupta, Shin, & Jain, 2023;Gurzki & Woisetschläger, 2017;Husain et al, 2021;Sun et al, 2014;Tunçel, 2022) Branding (Bilro et al, 2022;Creevey et al, 2022;Dhaliwal et al, 2020;Dubois et al, 2021;Gupta, Shin, & Jain, 2023;Gurzki & Woisetschläger, 2017;Husain et al, 2021;Kola nska-Stronka & Krasa, 2023;Kunz et al, 2020;Purohit et al, 2023;Shimul & Phau, 2022;Siahtiri et al, 2022) Counterfeiting (Gurzki & Woisetschläger, 2017;Husain et al, 2021;Shan et al, 2022;Tunçel, 2022) Sustainability (Atkinson & Kang, 2021;Kunz et al, 2020;…”
Section: Main Themes/drivers Scholarsunclassified
“…Existing research has identified an array of consumer‐level factors that influence demand for counterfeit or inauthentic products across different countries, include individual differences (e.g., Katyal et al, 2022), consumer motives (Le Roux et al, 2019), benign/ malicious envy (Gupta & Lyndem, 2024), moral and economic justifications (Poddar et al, 2012; Siahtiri et al, 2022), cognitive resources (Kim et al, 2012), brand personality perceptions (Bian & Moutinho, 2009), and need for belonging (Hang & Zhong, 2023; Zhang et al, 2023). Consumers, in many cases, are aware of their buying counterfeits through illegal channels for inferior quality at a low price.…”
Section: Literature Background and Conceptual Frameworkmentioning
confidence: 99%
“…Table 3 shows that no extremely high correlations exist among constructs, indicating no common method bias problem (Siahtiri et al, 2022) (see supplementary material).…”
Section: Measurement Modelmentioning
confidence: 99%